Penatalaksanaan Fisioterapi Pada Kasus Carpal Tunnel Syndrome Dekstra Di RSUD Saras Husada Purworejo - Amitamara, Baiq Deliga, Dwi Kurniawati, SSt., FT., M.Kes (2014)
Backround: Carpal Tunnel Syndrome (CTS) is a collection of symptoms that occur on the wrist to the finger due to the emphasis on the median nerve in the carpal tunnel current through (Carpal Tunnel). The pain and tingling (paraesthesia ) is manefestasi of this syndrome. Physiotherapy is a form of health care that is addressed to individuals and / or groups to develop , maintain and restore movement and function throughout the life span of the body using manual handling, improved motion, equipment (physical, and mechanical elektroterapeutis) training function, communication. Objective: To find Physiotherapy management in reducing pain and improving muscle strength in the case of Carpal Tunnel Syndrome (CTS) using Micro Wave Diathermy modalities (MWD), Ultrasound (US), Massage and Exercise therapy. Result: After therapy for 6 times the silent pain assessment results obtained from T0: 3 to T6: 1 , tenderness of T0: 5 to T6: 2, painful motion of T0: 5 to T6 :1, assessment of wrist flexor muscle strength T0: 4- become T6: 4 , wrist extensors T0: 4- become T6: 4 , radial deviation of T0: 4+ be T6: 4+ , ulnar deviation of T0: 4+ be T6: 4+. Conclution: Micro Wave Diathermy, Ultrasound, and massage can reduce pain, whereas Exercise therapy can improve muscle strength in Carpal Tunnel Syndrome Dekstra conditions.